The commercial promotion of electronic cigarettes on social media and its influence on positive perceptions of vaping and vaping behaviours in Anglophone countries: A scoping review. - L Chacon; G Mitchell; S Golder (Public Library of Science (PLoS), 2024)
There is ongoing scientific and policy debate about the role e-cigarettes play in tobacco control, with concerns centring around unknown long-term effects, and the potential industry co-option of harm reduction efforts, including marketing to youths. There is substantial evidence of the influence of conventional cigarette promotion on smoking behaviours in Anglophone countries, and the popularity of social networking sites, as well as the lack of marketing regulations on the commercial promotion of electronic cigarettes online, suggest an urgent need to explore this topic further. This scoping review aims to map the existing evidence related to the influence of e-cigarette commercial promotion on social media on positive perceptions of vaping and vaping behaviours in core Anglophone countries. Searches were conducted in CENTRAL, Cochrane Database of Systematic Reviews (CDSR), Embase, Epistemonikos, MEDLINE, PsycINFO and Science Citation Index, on the 21st of July 2022. From 1,385 studies, 11 articles were included in the final review, using diverse study designs, including focus groups, content analysis, cross-sectional studies, and experiments. The studies were primarily based in the U.S. and evidenced the association between the commercial promotion of e-cigarettes on social media with positive perceptions of vaping and vaping behaviours, particularly among young people, addressing diverse themes including celebrities' sponsorship, e-liquid appeal (including flavours and nicotine levels), users' engagement with ads, and other marketing strategies. Further, social networking sites commercially promoting e-cigarettes might increase positive attitudes towards vaping and vaping behaviours, particularly among youths. Future research should be conducted in broader settings, incorporate larger and diverse sample sizes, ensure research transparency, cover multiple social networking sites, emphasize ecological validity, and foment longitudinal studies.